Training and Assistance Digitization Making Learning Media use Google Apps for Education (GAFE ) for MTs Teachers throughout the District Purwakarta - Sidiq Aulia Rahman; Amit Saepul Malik; Machrus Alie; Arum Maslichah; Ike Kurniati; Mahmud Farid; Ikka Kartika Abbas Fauzi; Agus Mulyanto (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Activity devotion this aim for give knowledge , skills , and assistance making learning media using Google Workspace for Education for MTs teachers throughout the district Purwakarta . Activity devotion done in a manner stare advance live or offline on 7-8 November 2022 at MTs Al Muhajirin Purwakarta . Method used in dedication this use approach divided service learning Becomes two activity namely synchronous and asynchronous. Synchronous consists on delivery materials and questions answer about Google Apps for Education (GAFE ) , while asynchronous is in the form of guidance making digital learning media . Activity devotion started with stages pre activities and planning , stages implementation activities , stages of follow-up activities assistance , and stages evaluation . At stage pre activities and planning , carried out activity agreement with KKMTS and schools partner , then done studies introduction and analysis need with collect literature related digitization learning and use of learning media . At stages implementation done accompaniment making learning media , participants given knowledge about fast progress technology , important digital learning , and leveraging existing facilities _ provided by google. Participant given information related to Google Apps for Education (GAFE ) , and preparation of learning media , then participant design , arrange and deliver learning media draft . In the follow-up stage , learning media products are made by the participants then discussed _ to presenters and team for done assistance and revision . Meanwhile at the stages evaluation done charging questionnaire related implementation dedication and assistance . Devotion data collected through filling out digital learning media assistance surveys and results revision and filling questionnaire . Participant obtain knowledge about Google Apps for Education (GAFE ) and happened enhancement knowledge and skills in preparation of learning media digitally